Adverse Drug Reaction Tools Used in Causality Assessment - Kumaraswamy, Madaiah; Mohan, Akshay; Chonari, Thanveer Ahammed; Dahim, Muhammed (Indian Journal of Pharmacy Practice)
Adverse Drug Reactions (ADRs) tools are very significant in the detection, assessment, and severity of ADRs. This review emphasizes the most frequently utilized causality assessment scales, for example, the WHO-Uppsala Monitoring Centre Causality Assessment System, the Naranjo algorithm for the ADR assessment, the Liverpool Causality Assessment Tool (LCAT), and the Roussel Uclaf Causality Assessment Method (RUCAM). Bayesian Adverse Reactions Diagnostic Instrument (BARDI). In this review we found that the most commonly preferred tool is Naranjo Algorithm and the most commonly used combination is the WHO-Uppsala Monitoring Centre causality assessment system and the Naranjo algorithm. Large numbers of causality appraisal strategies have their benefits and burdens. In any case, Due to variation and inconsistency, no single causality assessment measure has been accepted and utilised globally. No single scale, however, has been accepted as standardised and taken into consideration for widespread acceptability.
Keywords: Adverse Drug Reaction; Causality assessment tools; Naranjo algorithm; WHO-Uppsala Monitoring Centre causality assessment system